(untitled) (Conferencea, 2023)
The UNIDROIT Principles of International Commercial Contracts (UPICC) is a set of rules for international commercial contracts created by the International Institute for the Unification of Private Law (UNIDROIT). The UPICC was first published in 1994 and has been updated twice since then, in 2004 and 2016. The principles have been widely used as a model for contractual relations between parties from different countries.